Negative Health Comparisons Decrease Affective and Cognitive Well-Being in Older Adults. Evidence from a Population-Based Longitudinal Study in Germany - Hajek, André; König, Hans-Helmut (Frontiers in Psychology, 2016)
Purpose: To examine the effect of health comparisons on affective and cognitive well-being in older adults longitudinally. Methods: Data were derived from the third and fourth wave of the German Ageing Survey (DEAS) which is a population-based prospective cohort study of community-dwelling subjects in Germany aged 40 and above (with 8,277 observations in fixed effects regressions). Health comparisons were assessed by the question “How would you rate your health compared with other people your age” (Much better; somewhat better; the same; somewhat worse, much worse). While affective well-being was quantified by using the Positive and Negative Affect Schedule (PANAS), cognitive well-being (CWB) was assessed by using the Satisfaction with Life Scale (SWLS). Fixed effects regressions were used to analyze the effect of health comparisons on affective and cognitive well-being. Results: While positive health comparisons only slightly increased CWB (total sample), negative health comparisons markedly decreased CWB (total sample and women) and negative affects (women). Neither positive nor negative health comparisons affected positive affects. Conclusions: Our findings stress the importance of negative health comparisons for CWB and negative affects in women. Comparison effects are asymmetric and in most cases upwards. Consequently, designing interventions to avoid upwards health comparisons might be a fruitful approach in order to maintain AWB and CWB.